The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.54327/set2023/v3.i1.56
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Signal Controller Optimization Through VISSIM to Minimize Traffic Congestion, CO and NOx Emissions, and Fuel Consumption

Dinakara Gunarathne,
Niranga Amarasingha,
Vasantha Wickramasighe

Abstract: In developing countries with heterogeneous traffic, such as Sri Lanka, it is possible to observe severe traffic congestion at intersections and traffic corridors. The main objective of this study was to demonstrate the optimization of traffic signal controllers using VISSIM microsimulation software. It aimed to minimize traffic congestion, emissions, and fuel consumption. This study focused on developing a traffic signal controller optimization program for a congested traffic corridor which consisted of a thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…The average number of vehicles observed was approximately 43,792. At Intersection J2, the highest number of vehicles was recorded on 24 August 2023, at 34,564, while the lowest was on 25 January 2023, at 28,308 The average number of vehicles observed was approximately 31,292. At Intersection J3 the highest number of vehicles was recorded on 28 December 2023, at 58,098, while the lowest was on 26 January 2023, at 39,067.…”
Section: Carsmentioning
confidence: 94%
See 1 more Smart Citation
“…The average number of vehicles observed was approximately 43,792. At Intersection J2, the highest number of vehicles was recorded on 24 August 2023, at 34,564, while the lowest was on 25 January 2023, at 28,308 The average number of vehicles observed was approximately 31,292. At Intersection J3 the highest number of vehicles was recorded on 28 December 2023, at 58,098, while the lowest was on 26 January 2023, at 39,067.…”
Section: Carsmentioning
confidence: 94%
“…Due to the diverse results of the previous stage of analysis, the microsimulation in PTV Vissim [26][27][28] will be based on the example of Intersection J3. The model includes three variants: with maximum intensity as indicated in the previous stage of analysis, minimum vehicle intensity, and average intensity from the entire study period.…”
Section: Microsimulation Analysismentioning
confidence: 99%
“…According to [11]. the VISSIM microsimulation software is the most well-known and often used of those.…”
Section: Traffic Signal Coordinationmentioning
confidence: 99%
“…From Mother Theresa intersection to Sarvanton intersection, travel time and delay were reduced after signal synchronization by 102.4 seconds and 110.32 seconds, respectively. The traffic signal controllers have been optimized for a congested corridor in Malabe town, Sri Lanka using Vissim software [11]. They found that emissions and fuel consumption were reduced by 14.89%.…”
Section: Introductionmentioning
confidence: 99%
“…Intersection saturation flow and intersection capacity are important parameters in planning and regulating traffic at highway intersections. Knowledge of intersection saturation flow is needed to calculate intersection capacity and plan efficient traffic management [6]. Traffic intersections, as road nodes, are also a major concern because they often cause conflicts between traffic participants [7].…”
mentioning
confidence: 99%